EFEKTIVITAS METODE JIBRIL DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN SANTRI DI WILAYAH AL-HUZAIMAH PONDOK PESANTREN AT-TAUFIQIYAH AENGBAJARAJA BLUTO SUMENEP - Fathorrahman Fathorrahman; Helminatul Hasanah (CV. Aksara Global, 2023)
The Jibril method is a method of reading the Qur'an which is done by Taqlid (imitating) where the teacher recites one verse of the Qur'an followed by another. Gabriel's method is one of the methods used to improve the ability to read the Koran. This study aims to determine the effectiveness of Jibril's Method in Improving Al-Qur'an Reading Ability. This research uses Quantitative method. The population in this study were students in the Al-Huzaimah Region of the At-Taufiqiyah Islamic Boarding School. Data was collected by distributing a questionnaire which was determined by means of a sample so that 168 respondents were obtained. Each given statement is measured using a Likert scale. Processing primary data using statistical analysis techniques Package for Social Science (SPSS) with the method of suspension and correlation test analysis. The results of this study indicate that the Gabriel Method is effective to be applied in improving students' Al-Qur'an reading skills. Which is obtained by looking at the results of the analysis performed.